Excess Thermodynamics of Mixtures Involving Xenon and Light Linear Alkanes by Computer Simulation - Palace Carvalho, Alfredo J. (2007)
Excess molar enthalpies and excess molar volumes as a function of composition for liquid mixtures of xenon + ethane (at 161.40 K), xenon + propane (at 161.40 K) and xenon + n-butane (at 182.34 K) have been obtained by Monte Carlo computer simulations and compared with available experimental data. Simulation conditions were chosen to closely match those of the corresponding experimental results. The TraPPE-UA force field was selected among other force fields to model all the alkanes studied, whereas the one-center Lennard−Jones potential from Bohn et al. was used for xenon. The calculated and for all systems are negative, increasing in magnitude as the alkane chain length increases. The results for these systems were compared with experimental data and with other theoretical calculations using the SAFT approach. An excellent agreement between simulation and experimental results was found for xenon + ethane system, whereas for the remaining two systems, some deviations that become progressively more significant as the alkane chain length increases were observed.